Improving Clothing Skills and Self-Esteem in Mentally Retarded Children with Self-Modelling Videos in Gondangrejo Karanganyar District: A Case Report - Endang Caturini Sulistyowati; Rita Benya Adriani; Happy Indri Hapsari; Nadya Puspita Adriana (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Children with mental retardation have below-average cognitive functions that can affect the overall level of intelligence, such as cognitive, motor, language, and social abilities. Improving skills in daily life, especially the use of clothing, is one of the important things that needs to be done. This case report aims to discuss how dressing skills and self-esteem in children with retardation with self-modeling videos. Subjects and Method: An 8-year-old child with moderate mental retardation has a learning disability with mild criteria, Initial complaints are known that the child has a dependence on parental assistance in terms of performing the skill of wearing clothes. Initial examination found that there was poor mental development which was characterized by low skills during the development period which affected cognitive ability, the patient also had a history of low self-esteem with a score of 12. Results: We reported the case of an 8-year-old child with moderate mental retardation who was given a self-modelling video to improve clothing and self-esteem skills. Patients were given modeling with videos that were assessed in 3 phases, namely the initial phase, the intervention phase, and the maintenance phase, the results showed an improvement curve in the ability to wear clothes and skills in patients. Conclusion: Self-modeling videos or Video Self Mondelin (VSM) is one of the effective and relatively simple interventions for children with mental retardation.